A review of scientifc linkages and interactions between climate change and air quality, with implications for air quality management in South Africa - Thambiran, Tirusha; Diab, Roseanne (South African Journal of Science, 2010)
In recent years there has been considerable advancement in our scientifc understanding of the linkages and interactions between climate change and air quality. A warmer, evolving climate is likely to have severe consequences for air quality due to impacts on pollution sources and meteorology. Climate-induced changes to sources of tropospheric ozone precursor gases and to atmospheric circulation are likely to lead to changes in both the concentration and dispersion of near-surface ozone that could act to offset improvements in air quality. The control of air pollutants through air quality management is also likely to impact on climate change, with reductions in ozone, particulate matter and sulphur dioxide being of particular interest. The improved understanding of the relationship between air quality and climate change provides a scientific basis for policy interventions. After a review of the scientific linkages, the potential to include climate change considerations in air quality management planning processes in South Africa was examined.